Chinese Media Delegations to Europe and the Reconstruction of Media Discourse on Europe in Post-Mao China (1978–1992). Issue 8 (14th September 2022) - Gan, Chun
Abstract: The years between 1978 and 1992 saw China enter a turbulent period of socio-economic recovery and foreign policy recalibration after the death of Mao Zedong. A string of organised expeditions to Europe by Chinese journalists produced a collection of first-hand, in-depth reportage, which vividly exemplified the reconstruction of Chinese media discourse on the outside world. Through an interdisciplinary lens, this article explores how the delegations formulated their discourses on Europe and argues that these discourses revealed a series of ideological and practical paradoxes that would continue to dominate China's perception of and strategies towards Europe far beyond 1992.